Can the rise in housing price lead to crime?: an empirical assessment of China - Song, Zhe (International journal of law, crime and justice, 2019)
The paper tries to estimate the impact of housing prices on criminal activities in China. An attempt is made to explore potential mechanism that links housing prices to crimes by using Utility Theory and Strain Theory. Both Static Panel Model and Dynamic Panel Model were used to estimate the relationship between housing prices and localized crimes in 28 provinces from China. The evidence supports that there exists a positive correlation between housing prices and criminal activities and the impact of housing prices on crimes varies from one region to another region in China.